2017
DOI: 10.5271/sjweh.3634
|View full text |Cite
|
Sign up to set email alerts
|

Exercise to reduce work-related fatigue among employees: a randomized controlled trial

Abstract: Exercise to reduce work-related fatigue among employees: a randomized controlled trial by de Vries JD, van Hooff MLM, Geurts SAE, Kompier MAJ This study shows that exercise has the potential to serve as a relatively simple and inexpensive secondary prevention strategy to improve (long-term) well-being among employees experiencing high work-related fatigue. The extent to which the exercise intervention under study caused beneficial effects in work-related fatigue depended on participants' compliance, underlinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 55 publications
6
57
0
9
Order By: Relevance
“…Thereby, exercise was individually tailored to each study participant ("intelligent physical exercise training") in considering physical fitness and work demands (Sjøgaard et al 2016). Another recent RCT showed a low-intensity running intervention was shown to reduce mental fatigue and the benefit was better when participation in running across six weeks was frequent (de Vries et al 2017). Moreover, an indirect positive effect of sports activities can be expected via increased unwinding and recovery experiences (de Bloom et al 2009).…”
Section: Recovery By Sports During Vacationmentioning
confidence: 99%
“…Thereby, exercise was individually tailored to each study participant ("intelligent physical exercise training") in considering physical fitness and work demands (Sjøgaard et al 2016). Another recent RCT showed a low-intensity running intervention was shown to reduce mental fatigue and the benefit was better when participation in running across six weeks was frequent (de Vries et al 2017). Moreover, an indirect positive effect of sports activities can be expected via increased unwinding and recovery experiences (de Bloom et al 2009).…”
Section: Recovery By Sports During Vacationmentioning
confidence: 99%
“…Likewise, Beck et al [30] showed that, following a physical activity intervention, impaired cognitive performance normalized. de Vries et al [31] showed in their intervention study that in the case of work-related fatigue, exercise does constitute a powerful medicine for those who comply with the treatment. In their systematic review, Naczenski et al [32] analyzed ten intervention studies and concluded that physical activity appears to be an effective means of reducing symptoms of burnout, though the quality of the methodology was not consistently satisfactory.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the heterogeneity of populations, assessment methods for both risk of burn-out and physical activity, and physical activity interventions, the vast majority of the experimental studies, including 5 RCTs, concluded that physical activity is effective in reducing the risk of burn-out, suggesting a causal link between both. The experimental studies showed a decrease in burn-out risk ranging from 6.9% to 41.3% [49,[52][53][54][55], a decrease in emotional exhaustion between 10% and 33.4% [47,48,51,56] and a decrease in cynicism of 33.3% and 4% [48,51]. One experimental study by Freitas et al [50], showing a relatively low quality score of 0.63, did not find any significant effect of physical activity on risk of burn-out.…”
Section: Discussionmentioning
confidence: 95%
“…However, one other study also assessed the effect of physical activity on emotional exhaustion, cynicism and personal accomplishment separately and did not find a significant effect on any dimension [50]. Two of the ten experimental studies assessed the effect of physical activity on emotional exhaustion only and showed a significant improvement in emotional exhaustion (−21.6% and −10%) [47,48].…”
Section: Physical Activitymentioning
confidence: 99%
See 1 more Smart Citation